Despising shame honor discourse and community maintenance in the Epistle to the Hebrews - deSilva, David Arthur (Atlanta, GA Scholars, 1995)
Includes bibliographical references and index.
Keywords: Rhetoric in the Bible; Bible. N.T. Hebrews -- criticism, interpretation, etc; Honour -- Biblical teaching